Creep and Fatigue Performance of Polymer Modified and Fibre Reinforced Bituminous Mixtures. - Napiah, Madzlan (2003)
The two principal modes of structural distress that occur in highway and road pavements as a result of traffic loading are deformation or rutting and cracking. Creep or deformation is caused by the deformation within the depth of the pavement. The accumulation of the permanent deformation within the road structure will cause rutting. Excessive rutting will normally lead to cracking, while the penetration of water and fines can result in the rapid damage of the pavement structure. Cracking in bituminous mixture, on the other hand is a fatigue phenomenon that depends upon the tensile strains induced in the material. This study involves some laboratory work on the deformation and fatigue characteristics of Hot- Rolled Asphalt (HRA) mixtures modified with polymer additives and fibres. The additives used were SBS and EVA whilst synthetic fibres used were polypropylene and polyester. The results of the study showed that mixtures containing polymer-modified binder gave a lower estimated rut depth compared to the conventional mixtures, indicating the superiority of these mixtures in creep. This was mainly due to the higher stiffness of the binder as being a major factor for such behaviour. This study also indicated that the higher porosity of the fibreincorporated mixes reduced the stiffness of the mixtures, thus reducing their resistance to long term deformation. However, should fibres be used for their superior fatigue behaviour, the creep tests showed that they should be incorporated at low concentrations to avoid problems relating to deformation. This seems to be the controlling parameter for the concentration of fibres when used in HRA mixtures. This study also showed that the incorporation of both polymer additives and synthetic fibres in bituminous mixtures have the potential of improving the fatigue performance of bituminous mixtures. Fatigue testing confirmed the strain capacity of these mixtures. In the case of the fibre-modified mixtures, this may be due to their higher bitumen content and thicker bitumen film coating the aggregates. The air void content of the fibre-reinforced mixtures were however greater than the normal mixtures. This is significant in that the fatigue performance would usually suffer when the air void is increased. The test results indicated that the fibre mixtures provided about the same fatigue performance as the control mixtures at low strain levels but at high strain levels, the fibre mixtures provided superior fatigue characteristics indicative that the fibre reinforced mixtures appear to be most beneficial at high strain levels.